An Analysis of Culture-Specific Items in the Turkish Translation of Shakespeare’s As You Like It by Halide Edip Adıvar and Vahit Turhan - Ercan Gürova (İstanbul Üniversitesi Çeviribilim Dergisi)
The main purpose of this study is to investigate the translation of culture-specific items in Shakespeare’s comedy As You Like It by Halide Edip Adıvar and Vahit Turhan. To this end, Javier Franco Aixela’s two major translation strategies (conservation and substitution) and sub-categories (repetition, orthographic adaptation, linguistic [non-cultural] translation, extratextual gloss, intratextual gloss, autonomous creation [source-culture origin], synonymy, limited universalization, absolute universalization, naturalization, deletion, autonomous creation [target-culture origin]) are employed for the classification and analysis of the randomly selected items from the play. The findings of this analysis are later discussed with the help of Venuti’s approaches to foreignization and domestication. Furthermore, the translation of culture-specific terms, the debates regarding the translator’s visibility, and their effects on the translation output are addressed. This study suggests that although both major strategies have been adopted during the translation process to a certain degree, the frequency of the domesticating strategies has outnumbered the frequency of the foreignizing strategy. This finding indicates that as macro-strategies of domestication are predominantly employed in the translation of As You Like It, the translators become invisible, which has created a false image of authorship. By employing the domesticating strategies predominantly, the foreignness of the text has been disrupted. Although employing domesticating strategies renders easy readability, this type of translation fails to fully appreciate the cultural differences between the source and target text.